Comparison of Blood Pressure before and after Exposure to Air Temperature in Fisherman Workers - Halijah, Siti; Susilawati, Susilawati; Susanti, Nofi (GLOBAL HEALTH SCIENCE GROUP, 2024)
The human body regulates its temperature to normal levels when exposed to cold temperatures, which allows it to adjust to changes in its surroundings. The force of blood that the heart pumps against the artery walls is called blood pressure. Variations in fishermen's blood pressure may be affected by the cold working environment. The purpose of this study was to determine the comparison of blood pressure before and after exposure to air temperature in fishermen workers. With a single group pretest-posttest quantitative research methodology, this study used an experimental pre-research design. Univariate data analysis, bivariate using the Wilcoson test and multivariate using MANOVA testing. The study population was 57 fishermen of Tanjung Tiram District. By using the basic random selection approach, the research sample amounted to 50 respondents. Data collection using primary data obtained directly from fishermen workers on the Tanjung Tiram coast using digital tension meters and observation sheets. The analytical tool used is SPSS. The results showed that there was a comparison of blood pressure before and after exposure to air temperature, meaning that exposure to air temperature can increase blood pressure both systole and diastole, so maintaining health is needed for workers who work as fishermen.